Spain : Financial Sector Reform: Third Progress Report. (IMF Staff Country Reports; Country Report ;, 2013)
This paper presents the Third Progress report on Spain's financial sector reform. Correction of Spain's large external, fiscal, and financial imbalances is well underway, with policy actions at both the European and Spanish levels helping to ease market pressures over the last year. Financial sector dynamics still contribute to recessionary pressures, with credit contraction accelerating, lending standards tightening, and lending rates to firms rising. Actions taken by the authorities under the European Stability Mechanism-supported program have helped tackle the legacy risk from the real estate boom bust, but macroeconomic risks still loom large.